Improving ambulatory saliva-sampling compliance in pregnant women: a randomized controlled study. - Julian Moeller; Roselind Lieb; Andrea H Meyer; Katharina Quack Loetscher; Bettina Krastel; Gunther Meinlschmidt (PLoS ONE)
Objective Noncompliance with scheduled ambulatory saliva sampling is common and has been associated with biased cortisol estimates in nonpregnant subjects. This study is the first to investigate in pregnant women strategies to improve ambulatory saliva-sampling compliance, and the association between sampling noncompliance and saliva cortisol estimates. Methods We instructed 64 pregnant women to collect eight scheduled saliva samples on two consecutive days each. Objective compliance with scheduled sampling times was assessed with a Medication Event Monitoring System and self-reported compliance with a paper-and-pencil diary. In a randomized controlled study, we estimated whether a disclosure intervention (informing women about objective compliance monitoring) and a reminder intervention (use of acoustical reminders) improved compliance. A mixed model analysis was used to estimate associations between women's objective compliance and their diurnal cortisol profiles, and between deviation from scheduled sampling and the cortisol concentration measured in the related sample. Results Self-reported compliance with a saliva-sampling protocol was 91%, and objective compliance was 70%. The disclosure intervention was associated with improved objective compliance (informed: 81%, noninformed: 60%), F(1,60)  = 17.64, p<0.001, but not the reminder intervention (reminders: 68%, without reminders: 72%), F(1,60) = 0.78, p = 0.379. Furthermore, a woman's increased objective compliance was associated with a higher diurnal cortisol profile, F(2,64)  = 8.22, p<0.001. Altered cortisol levels were observed in less objective compliant samples, F(1,705)  = 7.38, p = 0.007, with delayed sampling associated with lower cortisol levels. Conclusions The results suggest that in pregnant women, objective noncompliance with scheduled ambulatory saliva sampling is common and is associated with biased cortisol estimates. To improve sampling compliance, results suggest informing women about objective compliance monitoring but discourage use of acoustical reminders.